(untitled) (Journal of Naval Architecture and Marine Engineering, 2021)
The heat and mass transfer characteristics of the nonlinear, unsteady, radiative MHD boundary layer slip flow of a chemically reacting fluid past an infinite vertical porous plate are taken into account in this study. The effect of physical parameters are accounted for two distinct types of thermal boundary conditions namely prescribed uniform wall temperature thermal boundary condition and prescribed heat flux thermal boundary condition. Exact solution of the governing equations for the fluid velocity, temperature and concentration are obtained by using two term perturbation technique subject to physically appropriate boundary conditions. The expressions of skin friction, Nusselt number and Sherwood number are also derived. The numerical values of fluid velocity, temperature and concentration are displayed graphically whereas those of shear stress, rate of heat transfer and rate of mass transfer at the plate are presented in tabular form for various values of pertinent flow parameters. Results are compared with the literature in the limiting case.